Dual-Energy Low-keV or Single-Energy Low-kV CT for Endoleak Detection?: A 6-Reader Study in an Aortic Aneurysm Phantom. Issue 1 (January 2020) - Skawran, Stephan; Angst, Florian; Blüthgen, Christian; Eberhard, Matthias; Kälin, Pascal; Kobe, Adrian; Nagy, Daniel; Szucs-Farkas, Zsolt; Alkadhi, Hatem; Euler, André
Abstract : Objectives: The aim of this study was to compare image quality, conspicuity, and endoleak detection between single-energy low-kV images (SEIs) and dual-energy low-keV virtual monoenergetic images (VMIs+) in computed tomography angiography of the aorta after endovascular repair. Materials and Methods: An abdominal aortic aneurysm phantom simulating 36 endoleaks (2 densities; diameters: 2, 4, and 6 mm) in a medium- and large-sized patient was used. Each size was scanned using single-energy at 80 kVp (A) and 100 kVp (B), and dual-energy at 80/Sn150kVp for the medium (C) and 90/Sn150kVp for the large size (D). VMIs+ at 40 keV and 50 keV were reconstructed from protocols C and D. Radiation dose was 3 mGy for the medium and 6 mGy for the large size. Objective image quality and normalized noise power spectrum were determined. Subjective image quality, conspicuity, and sensitivity for endoleaks were independently assessed by 6 radiologists. Sensitivity was compared using Marascuilo procedure and Fisher exact test. Conspicuities were compared using Wilcoxon-matched pairs test, analysis of variance, and Tukey test. Results: The contrast-to-noise-ratio of the aorta was significantly higher for VMI+ compared with SEI ( P < 0.001). Noise power spectrum showed a higher noise magnitude and coarser texture in VMI+. Subjective image quality and overall conspicuity was lower for VMI+ compared with SEI ( P < 0.05). Sensitivity for endoleaks was overall higher in the medium phantom for SEI (60.9% for A, 62.2% for B) compared with VMI+ (54.2% for C, 49.3% for D) with significant differences between protocols B and D ( P < 0.05). In the large phantom, there was no significant difference in sensitivity among protocols ( P = 0.79), with highest rates for protocols B (31.4%) and C (31.7%). Conclusions: Our study indicates that low-keV VMI+ results in improved contrast-to-noise-ratio of the aorta, whereas noise properties, subjective image quality, conspicuity, and sensitivity for endoleaks were overall superior for SEI.